In-laws and Outlaws : Lessons in Research and Friendship and a Report from the Archives - Gordon, Sarah Barringer (Leonard J. Arrington Mormon history lecture series ;, 2007)
"I will talk about the three basic ingredients that have transformed my day job into a vocation: respect for the past, insight, generosity."--from p. 1.